Microstructure and properties of an advanced high-strength steel after austempering treatment. Issue 6 (13th April 2021) - Chen, Shangping; Mostert, Richard; Aarnts, Maxim
Abstract : The microstructure and mechanical properties were investigated as a function of the austempering temperature in an Si-rich advanced high-strength steel that is expected to serve for automotive applications. The results indicate that both the size and the morphology of bainitic ferrite vary with the austempering temperature. Incomplete bainite transformation was observed only in a limited temperature range. The strength of the steel is dominated by the ferrite size of the matrix including bainitic ferrite and martensite. The hole expansion capacity exhibits a positive correlation to the C content of retained austenite and a negative correlation to the amount of the retained austenite and the formation of carbides.